Dynamic osteosynthesis from stiff to biological fixation with graded moduli multilayer coatings on magnesium implant - Peng, Cheng (2015)
Over the years, osteosynthesis has been emphasizing mechanical stability of fragments to achieve stiff fixation, i.e., tight fixation of metallic implant. This, however, creates permanent stress-shielding because of the high modulus materials used (stainless steel or Ti implant), which easily leads to osteoporosis and even re-fracture after healing. Recent studies thus turn to flexible fixation using biologically degradable materials such as magnesium. This, however, deprives stiff fixation of the local stability advantage badly needed during early healing of bone tissues due to adopting low modulus of metallic magnesium. At present, Magnesium and its alloys attracted more concern of researchers on surface nano-crystallization, amorphization and coating for corrosion. The structure design of Mg implant is few that match healing process of bone. In this paper, the multilayer coatings of Fe/Zn are electroplated on Mg implant to take advantage of the biodegradability of Mg, Zn, Fe and the stiffness of Fe. In vivo study of the coated implant in rats suggests a combination of early stiff fixation and later stage biodegradation.